Examining factors influencing use of a decision aid in personnel selection - Jackson, Alexander Thomas (Kansas State University, 2016)
In this research, two studies were conducted to examine the factors influencing reliance on a decision aid in personnel selection decisions. Specifically, this study examined the effect of feedback, the validity of selection predictors, and the presence of a decision aid on the use of the decision aid in personnel selection decisions. The results of both studies demonstrate that when people are provided with the decision aid, their predictions were significantly more similar to (but not the same as) the predictions made by the aid than people who were not provided with the decision aid. This suggests that when people are provided with an aid, they will use it at least to some degree. This research also shows that when provided with a decision aid that has high validity, people will increase their reliance on the decision aid over multiple decisions. Finally, this research shows that, in general, there are individual differences that influence how participants weight the different selection predictors.
Keywords: Decision aid; Personnel selection; Decision making